The covenant - Michener, James A., 1907-1997 (London : Corgi Books, 1980)
"The Spellbinding story of the founding of South Africa-from the desolate beauty of its primitive origins, through the arrival of spirited European pioneers, to its expansion into a great, but tormented, modern State"